Comparative study to assess the effect of chewing stick and toothbrush on oral hygiene, gingival health and pocket depth among patients attending dental outpatient clinic in Udaipur, India - A. Agrawal; N. Bhatt; K. K. Shivlingesh; K. Singh; H. Chaudhary; S. Sen roy (Nigerian Dental Journal)
Objective: The purposes of this study was to assess and compare the oral hygiene, gingival health and pocket depth among patients using miswak (Salvadora Persica L) and toothbrush.